COMPARATIVE ANALYSIS OF THE FINANCIAL PERFORMANCE OF AUTOMOTIVE SUB-SECTOR MANUFACTURING COMPANIES LISTED ON THE INDONESIAN STOCK EXCHANGE (IDX) FOR THE PERIOD 2018-2021 - Adi Wijaya; Sri Hermuningsih (International Journal of Economics, Business and Accounting Research (IJEBAR), 2023)
This study aims to test and analyze "Comparative Analysis of the Financial Performance of Automotive Sub-Sector Manufacturing Companies Listed on the Indonesia Stock Exchange (IDX) for the 2018-2021 Period (Empirical Study of Pt. Astra International Tbk and Pt. Indomobil Sukses International Tbk). Characteristics used include Liquidity Ratio, Activity Ratio, Debt Ratio, Profitability Ratio and Market Ratio. Liquidity Ratio is based on Current Ratio and Quick Ratio, Activity Ratio is based on Fixed Asset Turnover Ratio (FATO), Debt Ratio is based on Debt Ratio, Profitability Ratio is proxied by Return On Asset (ROA) and Profit Margin (PM), and Market Ratio is prioritized by Earning Per Share (EPS) and Price Earning Ratio (PER). This study uses secondary data from financial reports and annual reports of companies included in the Automotive Sub-Sector Manufacturing companies during 2018-2021. Keywords: Liquidity Ratio, Activity Ratio, Debt Ratio, Profitability Ratio, and Market Ratio.